2004
DOI: 10.1093/sleep/27.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Tongue-muscle Training by Intraoral Electrical Neurostimulation in Patients with Obstructive Sleep Apnea

Abstract: Although tongue-muscle training cannot generally be recommended for the treatment of sleep apnea, the method has proven to be effective in the treatment of snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 36 publications
0
75
0
9
Order By: Relevance
“…Changes in morphology and proportion of fiber type consistent with muscle injury have been observed in the upper airway dilator muscles, both in animal models of OSA 15 and in OSA patients. 16 Randerath et al 5 found that training of the tongue muscles by electrostimulation was effective in reducing snoring in OSA patients. A significant reduction in symptoms and overall severity was demonstrated in patients with moderate OSA following an extensive oropharyngeal exercise program, derived from speech therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in morphology and proportion of fiber type consistent with muscle injury have been observed in the upper airway dilator muscles, both in animal models of OSA 15 and in OSA patients. 16 Randerath et al 5 found that training of the tongue muscles by electrostimulation was effective in reducing snoring in OSA patients. A significant reduction in symptoms and overall severity was demonstrated in patients with moderate OSA following an extensive oropharyngeal exercise program, derived from speech therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Mann and colleagues 4 demonstrated that electrical stimulation of the genioglossus muscle causes an increase in diameter of the hypopharyngeal airway. In a similar study, Randernath and associates 5 also showed that stimulation training of the tongue can be effective in reducing snoring, but they failed to fi nd an effect for OSA. Although it would be impractical to propose a similar electrical shock-based treatment for OSA at this time, these studies do suggest that increasing muscle tone of the upper airway could be benefi cial for patients with OSA.…”
mentioning
confidence: 95%
“…Preliminary results of case studies and one cohort showed improvements of the AHI, daytime sleepiness and snoring [122,123]. The only placebo-controlled double-blind study on tongue muscle training found an improvement of snoring but no significant reduction of AHI [124].…”
Section: Tongue Muscle Training By Electrical Stimulationmentioning
confidence: 99%
“…Although such approaches may lead to reduced severity of OSA for some patients, as is discussed below, given the heterogeneity of OSA pathogenesis such an approach will likely not resolve sleep-disordered breathing for all patients. Nonetheless, there is evidence to suggest that novel training exercises of upper airway muscles may lead to some improvement in sleep-disordered breathing (36,37). However, on the basis of the state dependence of OSA, muscle training during wakefulness is unlikely to have major effects on airway patency during sleep unless the increased muscle activity/efficiency is maintained during sleep.…”
Section: Upper Airway Dilator Muscle Activity and Reflex Responsivenessmentioning
confidence: 99%